2004
DOI: 10.1038/sj.cgt.7700746
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of Fas ligand gene therapy for the treatment of bladder cancer

Abstract: Previous investigations have revealed that bladder cancer cells are generally resistant to Fas-mediated apoptosis by conventional Fas agonists. However, the ability of these cell lines to undergo Fas-mediated apoptosis may have been underappreciated. As a result, we investigated the in vitro efficacy of Fas ligand gene therapy for bladder cancer. Three human bladder cancer lines (T24, J82, and 5637) were treated with the conventional Fas agonist CH-11, a monoclonal antibody to the Fas receptor. Cells were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Our initial approach was to develop tissue specificity of transgene expression, by using tissue or tumor-restricted promoters to regulate a TET-derived transcription factor (tTA) which drives transcription of the selected transgene (FasL, Apoptin, Bax or TRAIL) [1][2][3][4][5][6][7][8][9] (See Figure 1a). We successfully carried out such studies with adenoviral vectors and demonstrated restricted gene expression.…”
Section: Tissue-specific Expressionmentioning
confidence: 99%
“…Our initial approach was to develop tissue specificity of transgene expression, by using tissue or tumor-restricted promoters to regulate a TET-derived transcription factor (tTA) which drives transcription of the selected transgene (FasL, Apoptin, Bax or TRAIL) [1][2][3][4][5][6][7][8][9] (See Figure 1a). We successfully carried out such studies with adenoviral vectors and demonstrated restricted gene expression.…”
Section: Tissue-specific Expressionmentioning
confidence: 99%
“…Induction of apoptosis by AdGFPFasL has also been established in other CH-11 cancer resistant cells including prostate and bladder lines. 12,17 AdGFPFasL leads to significant tumor regression in vivo Although the SCC-14a cell line appeared to be quite sensitive to apoptotic induction by AdGFPFasL, it was not clear if the cells would behave similarly in an in vivo environment. To address this, an experiment was initiated to compare the growth of SCC-14a cells with and without AdGFPFasL treatment over a period of 3 months.…”
Section: Adgfpfasl Induces Characteristics Consistent With Fas-mediatmentioning
confidence: 99%
“…Apoptotic activity was assayed in parallel cultures using the Apo-ONE Homogeneous Caspase 3/7 Apoptosis Assay (Promega, Madison, WI, USA) according to the manufacturer's instructions. 38,39 Hh-Responsive Luciferase Reporter Assay…”
Section: Cell Viability and Apoptosis Assaysmentioning
confidence: 99%